Pengaruh Karakteristik Perusahaan Manufaktur Terhadap Pengungkapan Corporate Social Responsibility (CSR) Serta Dampaknya Terhadap Reaksi Investor - Astuti, Rachmawati Nur Puji; , Dra. Rina Trisnawati, Ak, M.si Ph.D (2015)
The aim of this research is to analyze the influence of firm characteristics that are the company size, leverage, company profile, size of commissioner board and public ownership on the corporate social responsibility (CSR) disclosure and the effect of the corporate social responsibility (CSR) disclosure to investor reaction which is measured by abnormal return. The measurement of corporate social responsibility based on the Global Reporting Intiatives disclosure index (GRI) 2013 with 149 items. The population of this research is all manufacture companies listed on the Indonesia Stock Exchange (IDX) during 2010-2013 period. This sample research is 72 annual reports which obtained by purposive sampling. The research used secondary data sourced from www.idx.co.id, while the list of stock price and the stock price index obtained from yahoo finance.com. Data analysis used multiple linear regression method. The results indicate that company size, leverage and company profiles have a significant effect on the corporate social responsibility (CSR) disclosure. Meanwhile, the size of commissioners board and public ownership don't have significant effect on the corporate social responsibility (CSR) disclosure. Corporate social responsibility (CSR) disclosure has a significant effect on investor reaction